Papéis ocupacionais e aspectos psicossociais de mães de crianças com síndrome congênita do zika vírus - Reis, Monique Carla da Silva (2020)
The Zika Congenital Syndrome (ZCS), characterized by a spectrum of changes that includes besides microcephaly, visual and hearing impairment, epilepsy, neuromotor and cognitive impairment. The functional limitations and long-term dependence of these children may lead to changes in maternal occupational roles and have a negative impact on the mothers' wellbeing and mental health. In addition, a possible new Zika virus (ZIKV) epidemic will affect the desire and planning for a new pregnancy. This thesis aimed to (1) analyze the changes in occupational roles and their consequences on the mental health of mothers of children with ZIKV and (2) assess the level of concern among women of reproductive age about a new ZIKV epidemic and its influence on the intention of a new pregnancy. Both studies were crosssectional observational. The first study included 40 mothers of children with SCZ from the state of Alagoas. The functions performed by these mothers were evaluated from the Occupational Paper Identification List and the presence of Common Mental Disorder (CMD) by the Self- Reporting Questionnaire (SRQ-20). The relationship between CMD and changes in occupational roles was analyzed using a standard logistic regression model. The second counted with 123 women, being 33 mothers of children with ZCS and 90 mothers of healthy children from the states of Alagoas and Sergipe. The level of concern about a possible new ZIKV epidemic was assessed through a questionnaire created by the researchers containing five questions, which were answered using a five-point Likert scale. Two additional questions were used to assess the intention of a new pregnancy and the influence of a new ZIKV epidemic on the intention of a new pregnancy. For this second study, Mann-Whitney and Chisquare tests were used. Faced with the sample analyzed in the first study, most mothers (n=40) reported loss of their occupational roles after the birth of the child. The most affected roles were that of student (-77.8%), paid worker (-76.5%), volunteer (-75.0%), friend (-39.4%) and hobby (-35.3%), while increasing their role as caregiver (+ 44.4%) and participation in organizations (+ 150.0%). As for mental health, evaluated through the Brazilian version of the, twenty-three (57.5%) mothers presented positive symptoms for CMD. The logistic regression analysis showed significant association between CMD and loss of paid work after child birth (p = 0.026). In the second study, the results showed that mothers of children with ZCS present higher levels of concern with a new epidemic and insecurity with health care provided in public service. In both groups, there was a decrease in the intention of a future pregnancy due to the fear of ZIKV infection. The results of this research demonstrated the need to think about the ZIKV epidemic in addition to the child's sequelae, considering that their mothers suffer from the consequences of reducing their occupational roles, spending most of their time caring for and accompanying their child in therapies, making it impossible for them to have paid work, affecting their mental health. In addition, our results suggest that a possible new epidemic may affect the decision to have a new pregnancy, both among mothers of healthy children and in mothers of children affected by ZCS.